Incorporation of copper-doped mesoporous bioactive glass nanospheres in experimental dental composites: Chemical and mechanical characterization - Marovic, Danijela; Haugen, Håvard J.; Negovetic Mandic, Visnja; Par, Matej; Zheng, Kai; Tarle, Zrinka; Boccaccini, Aldo R. (Materials, 2021)
Experimental dental resin composites incorporating copper-doped mesoporous bioactive glass nanospheres (Cu-MBGN) were designed to impart antibacterial and remineralizing properties. The study evaluated the influence of Cu-MBGN on the mechanical properties and photopolymer-ization of resin composites. Cu-MBGN were synthesized using a microemulsion-assisted sol–gel method. Increasing amounts of Cu-MBGN (0, 1, 5, and 10 wt %) were added to the organic polymer matrix with inert glass micro-and nanofillers while maintaining a constant resin/filler ratio. Six tests were performed: X-ray diffraction, scanning electron microscopy, flexural strength (FS), flexural modulus (FM), Vickers microhardness (MH), and degree of conversion (DC). FS and MH of Cu-MBGN composites with silica fillers showed no deterioration with aging, with statistically similar results at 1 and 28 days. FM was not influenced by the addition of Cu-MBGN but was reduced for all tested materials after 28 days. The specimens with 1 and 5% Cu-MBGN had the highest FS, FM, MH, and DC values at 28 days, while controls with 45S5 bioactive glass had the lowest FM, FS, and MH. DC was high for all materials (83.7–93.0%). Cu-MBGN composites with silica have a potential for clinical implementation due to high DC and good mechanical properties with adequate resistance to aging.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Bioactive glass; Copper; Dental; Mesoporous; Nanoparticles; Resin composites